IBN KHALDŪN’S CONCEPT OF MALAKAH AND THE TRI-DIMENSIONAL EDUCATIONAL MODEL: A HERMENEUTIC RECONSTRUCTION FOR INTEGRATED CURRICULUM DESIGN - Mokhammad Ainul Yaqin; Mahtumridho Ghufron Bin Simun (Institut Bahri Asyiq Galis Bangkalan, 2026)
This article presents a systematic reconstruction of Ibn Khaldūn's educational philosophy as an integrated tri-dimensional model grounded in the concept of malakah a deeply ingrained, embodied skilled disposition acquired through sustained, deliberate practice. Drawing on philosophical hermeneutics and close analysis of the Muqaddimah, the study identifies three interdependent dimensions of Ibn Khaldūn's pedagogical thought: intellectual development through gradual, sequenced instruction (al-tadrīj fī al-taʿlīm); moral formation through the cultivation of virtuous dispositions (tahdhīb al-akhlāq); and experiential mastery through direct, embodied practice (tajriba). The article demonstrates that these dimensions are not separate topics but mutually qualifying components of a coherent educational architecture unified by the principle of malakah. Six formal propositions are developed to articulate the internal logic of the framework, and the model is critically situated in dialogue with contemporary educational theories including constructivism, experiential learning, character education, competency-based education, and critical pedagogy. The findings contribute to Islamic educational philosophy, comparative education, and ongoing efforts to decolonise curriculum theory by recovering non-Western conceptual resources. The article concludes with implications for curriculum design, teacher education, assessment practice, and educational policy, and proposes an agenda for empirical research on the application of the malakah framework in diverse educational settings.